Modeling the impact of players` workload on the injury-burden of English Premier League football clubs - Fuller, C. W. (Scandinavian Journal of Medicine & Science in Sports, 2018)
The loss of players through injury is known to affect team performance in many sports; it is important, therefore, for professional teams to be able to quantify the likely injury-burden that will be encountered throughout a season. A kinetic model, based on the rates at which match and training injuries are sustained and resolved, a team's squad size and the 2017/2018 season fixture schedule for teams competing in the English Premier League, is used to produce daily forecasts of injury-burden experienced by a typical team. The incidences and median severities of match (incidence: 26.9 injuries/1000 player-match hours, 95% CI: 21.5-33.7; severity: 17.5 days, 95% CI: 13.0-28.0) and training (incidence: 4.3 injuries/1000 player-training hours, 95% CI: 3.4-5.5; severity: 14.0 days, 95% CI: 11.0-22.0) injuries were determined using data collected from four English Premier League football clubs during the 2016/2017 season. Time-to-recovery curves for the match and training injuries sustained in the Premier League closely matched the time-to-recovery curves predicted by the kinetic model used in this study. The kinetic model predicted higher match and lower training injury burdens and a higher overall injury burden for successful teams competing in both national and European club competitions compared to teams competing only in national competitions. The model also showed that, in terms of injury-burden, there were no benefits in adopting a 4-week mid-season break during the season: reducing the number of clubs competing in the Premier League would, however, reduce the overall injury burden during a season.